Electrical engineer's portable handbook - Hickey, Robert B. (McGraw-Hill, 1999)
This quick-look-up working tool, packed with tables, charts, and checklists, takes the guesswork out of almost any electrical design task or calculation. Indispensable for electrical engineers, designers, and technicians, the Handbook provides immediate fingertip access to the fundamental information busy professionals need for everyday use in the field.